KAJIAN KUALITAS JAHE EMPRIT (ZINGIBER OFFICINALE VAR. AMARUM) MELALUI SKRINING FITOKIMIA - Nurhidayati Harun; Nia Kurniasih; Ernawati Kurniasih (Publikasi oleh Fakultas Kedokteran Universitas Islam Malang, 2024)
ABSTRACTJahe emprit (Zingiber officinale var. amarum) is a variety of ginger that contains secondary metabolites such as flavonoids, alkaloids, saponins, and tannins, which have potential as raw materials in pharmaceutical formulations and herbal products. This study aims to evaluate the phytochemical and physicochemical quality of jahe emprit and identify its potential as a raw material for pharmaceutical preparations.The research was conducted using a maceration method with 70% ethanol as a solvent, followed by non-specific quality tests (moisture content, ash content, and yield) and specific tests (phytochemical screening). The process of making the extract powder was carried out using a drying method with Avicel pH 101 as a carrier agent.The results showed that the jahe emprit extract met quality parameters according to the standards. Phytochemical testing confirmed the presence of flavonoids, alkaloids, saponins, and tannins, which support its potential as an antioxidant, anti-inflammatory, and antimicrobial agent. The resulting dry extract powder exhibited good flow properties and stability of bioactive compounds, making it suitable for pharmaceutical applications.The conclusion of this study is that jahe emprit has phytochemical and physicochemical qualities that meet the criteria for high-quality herbal raw materials. It is recommended that further research focus on clinical testing and the development of jahe emprit-based product formulations to enhance its added value in the pharmaceutical and herbal industries.Keywords: Jahe emprit; Zingiber officinale var. amarum; phytochemistry; pharmaceutical formulation.